Methods for the health technology assessment of complex interventions: A scoping review - Abdolvahab Baghbanian; Drew Carter; Tracy Merlin (PLoS ONE, 2025)
Introduction Health Technology Assessment (HTA) methods have been developed to support evidence-informed policy-making by assessing the comparative value and costs of health interventions and programs. However, the complexity of many health interventions presents challenges to the use of conventional HTA methods. This scoping review collated and synthesised international approaches to the HTA of complex interventions including identifying assessment criteria, types of evidence and the domains of value that are most favoured. Materials and methods A systematic scoping review was conducted using JBI guidelines, Arksey and O’Malley’s six-stage framework and recent advances in scoping review methodology. Seven electronic databases, grey literature sources, three leading HTA journals and backward citation searching were used to search complex intervention HTA records written in English from January 2000 to December 2023. Supplementary searches were also conducted to identify actual HTA reports produced by certain countries. The Population (or Participants), Concept and Context framework guided the literature selection process, with a two-phase screening process and subsequent narrative synthesis. The PRISMA-ScR checklist guided reporting. Independent screening by two reviewers ensured accuracy of study selection, and data extraction followed a customised form grounded in the HTA-core model. Results A total of 10684 references yielded 35 records from twelve countries. The review identified two clusters of research on HTA of complex interventions: methodological orientation and conceptual models (n = 19) and actual HTAs conducted on complex interventions (n = 16). Several evaluation criteria and domains were used or recommended for use that extended beyond the core HTA domains. Three distinct HTA approaches emerged: the integrative approach, highlighted in methodological guides and theoretical frameworks; and either sequential or concurrent approaches, emphasised in practical HTAs. In the theoretical literature, equal weight is given to various HTA domains for complex intervention assessment, but in practice, the scope and specificity of domains vary across reports, with countries exhibiting differing priorities. Cost-effectiveness, clinical effectiveness and organisational aspects predominated in complex intervention evaluation, albeit with gradually increasing emphasis on a technology’s description, intended use, safety and patient and social aspects over the past decade. There was less focus on ethical and legal considerations. This trend is consistent with the evaluation of non-complex interventions in HTA. HTAs undertaken on complex interventions introduced unique domains like politics, implementation, early stakeholder engagement, outcome uncertainty, adaptive methods and real-world data, with expert opinion recommended when data were insufficient. Conclusion A shift towards considering broader contextual and implementation factors in the HTA of complex interventions was evident in this scoping review, extending beyond traditional HTA domains. However, discrepancies persist between theoretical and methodological guidance suggesting one approach and practical HTAs often adopting another. The implications of the shift towards contextual and implementation factors require exploration in future research. This could help to establish consensus on metrics and evidentiary elements, optimising HTA for complex health interventions.